Sensitization to oil palm pollen associates with risks and severity of allergic diseases - Sio, Yang Yie; Nanong, Gallego Allaine Victoria; Lim, Jie Ann; Matta, Sri Anusha; Say, Yee How*; Teh, Keng Foo *; Wong, Yi Ru *; Smyrna Moti, Rawanan Shah *; Kavita, Reginald *; Chew, Fook Tim (Elsevier, 2024)
Background: Elaeis guineensis (Ela g, oil palm) pollen is one of the most predominant species of inhalant allergens in the tropical Southeast Asia region; however, its association with the manifestation of allergic diseases remains largely unexplored. This study aimed to determine the sensitization pattern of oil palm pollen and associate this with the risk and severity of allergic diseases.